Gel actuators based on polymeric radicals. Issue 57 (17th October 2019) - Wickramasinhage, Ravindra N.; Goswami, Shailesh K.; McAdam, C. John; Malik, Sharali; Hanton, Lyall R.; Moratti, Stephen C.
Abstract : Reversible actuation of a radical-gel over many cycles with large strain. Abstract : Low-voltage electrochemical actuation of radical polymer gels has been demonstrated in an organic electrolyte. Polymer gels were prepared by post-modification of active-ester precursor gels with an amine-functionalised radical. A combination of few-layer graphene and multiwall carbon nanotubes gave high conductivity and improved actuation in the gels, with 32% linear actuation. The actuator system showed good stability over at least 10 cycles, showing its promise. The cycle time was several hours due to mass-transport limited transport of ions and solvent into the device.